Yugowave and Serbwave on Youtube - Bobnič, Robert (Družboslovne razprave, 2025)
The article examines the phenomenon of Yugowave, including its offshoots, on the YouTube platform. As an online audiovisual genre, which originated from vaporwave and eventually developed independently, it serves as a remediation of collective memory, featuring nostalgic references to the era of the Socialist Federal Republic of Yugoslavia, or the war conflicts that followed its dissolution. Drawing on data from 426 videos and 14,344 comments, we examine the genre’s evolution and map audience communities using the Leiden method on a bipartite network linking commenters to their public YouTube subscriptions. The analysis suggests that the war aesthetics of Serbwave prevail among the videos and its commenters may be described as a wide international audience, predominately holding interests in history, militarism and gaming
Keywords: community; community detection; detekcija skupnosti; Serbwave; Skupnost; vaporwave; You Tube; YouTube (spletno mesto); Yugowave